CO2 LASER HEAD NOZZLE FLOW ANALYSIS AND MODERNIZATION - Suckovs, Ilja; Rudziss, Raitis; Zaicevs, Edgars (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2021)
With the passage of time and the development of technology, more applications are found in CNC controls with CO2 laser equipment. Laser machines with a CO2 source are increasingly distributed in woodworking and synthetic materials processing. Laser equipment makes it possible to produce high-quality and geometrically accurate products. The quality of the surface to be processed is directly related to the air flow intensity, which prevents sublimated particles burn to processed surface. The aim of the study is to increase air flow intensity by upgrading the internal design of the head nozzle. Simulations are created for modernized head nozzle that help to analyze the resulting data. Cutting and engraving is performed for wood material in working range for the head nozzle tests.